2001
DOI: 10.1016/s0033-3549(04)50074-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between premature mortality and socioeconomic factors in black and white populations of US metropolitan areas

Abstract: SYNOPSISObjective. This ecologic study examined the association of mortality with selected socioeconomic indicators of inequality and segregation among blacks and whites younger than age 65 in 267 US metropolitan areas. The primary aim of the analysis was to operationalize the concept of institutional racism in public health.Methods. Socioeconomic indicators were drawn from Census and vital statistics data for 1989-1991 and included median household income; two measures of income inequality; percentage of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…Much research into the causes of racial disparity in health in the United States has focused on individual attributes. 44,48,56 However, there is a growing recognition of the importance of contextual characteristics in local health disparities. 44,46,57,58 As David Williams has written: “Effective effort to reduce racial disparities in health status should seriously grapple with … targeting interventions not only at individuals but also at the geographic context within which they live.” 46 …”
Section: Discussionmentioning
confidence: 99%
“…Much research into the causes of racial disparity in health in the United States has focused on individual attributes. 44,48,56 However, there is a growing recognition of the importance of contextual characteristics in local health disparities. 44,46,57,58 As David Williams has written: “Effective effort to reduce racial disparities in health status should seriously grapple with … targeting interventions not only at individuals but also at the geographic context within which they live.” 46 …”
Section: Discussionmentioning
confidence: 99%
“…Age differences across studies may also play a role, particularly if among older populations mortality selection is operating to cull Blacks such that only hearty Blacks had survived to participate in the sample. Since mortality selection may be especially operative in predominantly Black neighborhoods, 9, 11 this could explain the apparent protective effect of racial composition with CVD mortality seen in previous studies of adults ages 65 and older.…”
Section: Discussionmentioning
confidence: 98%
“…Despite an extensive literature examining the association between racial residential segregation and health outcomes, studies of neighborhood racial composition are relatively sparse and those that exist rarely examine mediating factors. Interestingly, while ecological studies of large areas (e.g., states, counties) have generally demonstrated a positive correlation between the percentage of blacks in the area and mortality rates (Bird, 1995; Cooper et al, 2001; Deaton & Lubotsky, 2003; McLaughlin & Stokes, 2002), studies of smaller areas, and multi-level studies using individual-level outcomes, have had mixed results. Studies of New York City have demonstrated lower mortality for elderly blacks, Hispanics, and whites living in neighborhoods with higher proportions of their respective racial group (Fang et al, 1998; Inagami et al, 2006), but worse self-reported health status for blacks who live in neighborhoods with a greater proportion of black residents (White & Borrell, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrate that higher proportions of blacks in a geographic area are associated with higher mortality (Bird, 1995; Cooper et al, 2001; Deaton & Lubotsky, 2003; McLaughlin & Stokes, 2002) and worse self-reported health status (White & Borrell, 2006), often for both blacks and whites. However, many of these studies do not adjust for other individual or area-level sociodemographic characteristics, limiting the insight into independent effects of racial composition.…”
Section: Introductionmentioning
confidence: 99%